1973
DOI: 10.2514/3.6740
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of eigenvalues and eigenvectors in non-self-adjoint systems.

Abstract: U 1 = J r |_e f j [D] {s} dV; and D = matrix relating stress to elastic strain, e = total strain, s 1 = pseudo initial strain.The integrals are over the undeformed (or initial) body and can readily be evaluated. Expanding Eq. (1) yields an expression of the form dV (2)Neglecting plasticity, temperature, and other similar effects, the total strain is the sum of the elastic and initial strains, or e^e' + s 1 (3) Treating the initial strain as a constant during the variation of the total strain results in the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(56 citation statements)
references
References 5 publications
0
56
0
Order By: Relevance
“…Therefore the rate-dependent terms in the equation of motion in Eq. (20) can be neglected, resulting in the linear system…”
Section: Divergencementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the rate-dependent terms in the equation of motion in Eq. (20) can be neglected, resulting in the linear system…”
Section: Divergencementioning
confidence: 99%
“…IV.C. Using the system matrix sensitivities, the eigenvalue derivatives are computed as elaborated in [20]. This requires the computation of the left and right eigenvector as well as the computation of the derivatives of the right eigenvector corresponding to the smallest eigenvalue.…”
Section: A Sensitivities Of the Divergence Pointmentioning
confidence: 99%
“…Differentiating Equation (1) with respect to x k , and x l , Plaut and Huseyin [43] have shown that, providing the eigenvalues are distinct, …”
Section: Random Matrix Eigenvalue Problemsmentioning
confidence: 99%
“…In contrast with symmetric undamped systems, many complications are encountered in calculating the eigenderivatives of an asymmetric non-conservative system for which the eigenvalues and eigenvectors are complex and the right and left eigenvectors are distinct. The first general expressions for eigenvalue and eigenvector derivatives for non-self-adjoint systems were studied using the modal approximation by Plaut and Huseyn [11]. Later, many other researchers have modified the modal method to account for conservative or non-conservative asymmetric systems.…”
Section: Introductionmentioning
confidence: 99%